Seven years in Dostoevsky's Crime and Punishment. Issue 1 (10th May 2021) - Yoon, Saera
Abstract: In studies of Crime and Punishment, the role of Svidrigailov as Raskolnikov's negative double has been widely discussed, but relatively little attention has been paid to the temporal motifs in the connection between the two characters. The lacuna is surprising given the sense of time is acutely palpable in the novel. The aim of this article is to examine Dostoevsky's utilization of temporal motifs of seven years, which will cast new light on how Raskolnikov's story is constructed in contrast to Svidrigailov's. In both Raskolnikov's and Svidrigailov's narratives the motif of seven years stands out: they both are sent away from the capital city for seven years, but the ways in which they experience those seven years reveal their crucial differences in their destinies. If Svidrigailov's seven years in the country is the past permeated with boredom, Raskolnikov's is future-oriented, rich in the expectations of suffering, future deeds and spiritual resurrection. Another noteworthy difference lies in the role of the women who are expected to save them. Raskolnikov's seven years in Siberia is better appreciated against the backdrop of Svidrigailov's eschatological time ending with the death of his wife and subsequently, his own.